A Pragmatic Study of Gestural Strategies in English Sport TV Interviews - Zainab Mohammed Radhi; Atyaf Hassan Ibrahim; Liqaa Habeb Al-Obaydi (JELITA, 2022)
Gestures and speech are significant features that collaborate to create meaning in an interaction. The current study aims to investigate the use of these gestural strategies in English sport TV interviews. This study is based on the hypothesis that interlocutors in TV interviews employ various gesture strategies. The selected interviews have been analyzed in the light of an eclectic model based on model Kulkarni (2013) and Searle (1979). The former is used to analyze the various types of body movements and gesticulation, while the latter is used to analyze gestures as speech acts. The results of the selected interviews revealed that gestural strategies are closely tied to the context of situation. Each gesture performs a specific speech act. The interlocutors in sport interviews express their feelings and attitudes through gestures in an efficient manner. They use gestures to express agreement, openness, sympathy, grief and anxiety. In sport interviews, the interlocutors use gestures freely by moving their hands, arms, heads, and every other part of their bodies.